Students in Library Science and Information Studies at UNAM under a new teaching modality derived from COVID-19 - Guevara Villanueva, Angélica; Rosas Gutiérrez, Angélica María; Cabral Vargas, Brenda (Revista General de Información y Documentación, 2021)
This article focuses its interest in the students of the school system of the Bachelor of Librarianship and Information Studies of the Faculty of Philosophy and Letters of the UNAM, in the face of two scenarios that affected their academic life: the end of their semester and the beginning of one semester abnormally. The first, derived from a student strike and the second, with bigger impact, produced by the indefinite closure of its faculty due to the pandemic caused by COVID-19. The general objective of the research is to describe the experiences of the school population of the bachelor's degree in library science and information studies, faced with the personal decision to start their semester in the emerging modality of distance education during confinement due to the COVID pandemic. -19. The research follows a mixed descriptive and quantitative methodology. The data were collected through a questionnaire that was applied online to students who were about to conclude the 2020-II school semester. Some of the results show that the students experienced various circumstances such as caring for a sick relative, the lack of a physical space to develop their school activities and an increase in stress and anxiety in the face of new family dynamics.
Keywords: Long distance education; University students; COVID-19; College of Library Science; Faculty of Philosophy and Letters